Review on Pollution Monitoring Systems - Dash, Aditya; Kumar Nanda, Manas (International Journal of Psychosocial Rehabilitation, 2025)
Toxic components that have affected the balance of the ecosystem. The inappropriate persecution of such components has directed to an intensification in pollution of the fundamental elements of the ecological system that serve as a model for the looking after of human existence. Detecting contamination in a timely manner and finding the source of pollution is of paramount importa nce to sustainable development. These are roundabout of the key issues related to the preservation of harmonious coexistence among human beings and the environment. The emerging infrastructure of the Internet of Things and cloud computing offers a range of potential batch templates for the reasons set out above. The preceding paper puts light on certain of the systems surveyed and compares them all in order to investigate zones of advancement and relocate towards a better, additional robust and more convenient system for the same economic model.